2022
DOI: 10.1039/d2mo00036a
|View full text |Cite|
|
Sign up to set email alerts
|

Metabolomics study reveals the alteration of fatty acid oxidation in the hearts of diabetic mice by empagliflozin

Abstract: Empagliflozin (Empa, SGLT2 inhibitor), is widely used in clinical situation for the management of diabetes. It has beneficial effects in reducing cardiac dysfunction and heart failure. However, rare studies had...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Curiously, in diabetic recipients, there was observed lipotoxic cardiomyocyte dysfunction associated with peroxisome proliferator-activated receptors-g (PPAR-g) overexpression, which could be reduced with the SGLT2is [ 90 ]. In a recent study conducted by Zhang et al, empagliflozin targeted the mitochondrial fatty acid oxidation pathway, which is altered in db/db mice hearts [ 91 ]. SGLT2i has been reported to induce phospho-AMP-activated protein kinase alpha 2 (pAMPKalpha2), which is responsible for metabolic switching from fatty acids and maintenance of energy balance [ 88 ].…”
Section: Sglt-2is In Dc—the Overview Of Research Resultsmentioning
confidence: 99%
“…Curiously, in diabetic recipients, there was observed lipotoxic cardiomyocyte dysfunction associated with peroxisome proliferator-activated receptors-g (PPAR-g) overexpression, which could be reduced with the SGLT2is [ 90 ]. In a recent study conducted by Zhang et al, empagliflozin targeted the mitochondrial fatty acid oxidation pathway, which is altered in db/db mice hearts [ 91 ]. SGLT2i has been reported to induce phospho-AMP-activated protein kinase alpha 2 (pAMPKalpha2), which is responsible for metabolic switching from fatty acids and maintenance of energy balance [ 88 ].…”
Section: Sglt-2is In Dc—the Overview Of Research Resultsmentioning
confidence: 99%
“…14,73,74 Our study illuminates a central role of the microbiome and metabolic and early proximal tubule reconfiguration. Whereas several studies have explored the long-term effects on other tissues, [75][76][77] we focused on relatively healthy mice at early time points to avoid dominating secondary omics signals from fibrosis, serum responses, and tissue decay that hamper mechanistic interpretation of omics data. 78 SGLT2i had larger effects on metabolism and kidney reconfiguration in nondiabetic mice than in hyperglycemic Akita mice.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that dapagliflozin therapy mobilizes FFAs from adipose tissue and increases hepatic FFA oxidation in diabetic animals 83 . Empagliflozin was also able to increase lipid peroxidation in diabetic mice 84 . Moreover, dapagliflozin increased lipid peroxidation and ketone body levels in T2DM patients 85 .…”
Section: Pathophysiology Of Sglt2i‐induced Acidosismentioning
confidence: 99%
“…83 Empagliflozin was also able to increase lipid peroxidation in diabetic mice. 84 Moreover, dapagliflozin increased lipid peroxidation and ketone body levels in T2DM patients. 85 Therefore, induction and promotion of FFA beta-oxidation is the main link between SGLT2is and DKA.…”
Section: Linked Mechanisms Effects On Ketogenesis Referencesmentioning
confidence: 99%